Kematangan Postural Control dan Kaitannya dengan Attention serta Kesiapan Belajar Anak Usia Dini - Iftitahun Nabilah; Umarul Faruk (Institut Agama Islam Tarbiyatut Tholabah, 2026)
The phenomenon of young children still experiencing difficulty maintaining postural stability and focusing attention during learning demonstrates the urgency of studying the relationship between postural control maturity and attention and learning readiness. This study aims to examine and synthesize literature on the relationship between postural control maturity and attention and learning readiness in young children. The findings of this study found that motor skills, particularly balance, which is part of postural control maturity, are positively related to attention and cognitive abilities that support learning readiness in young children. Other research findings revealed that increased postural demands do not impair cognitive performance, but a stable postural condition further supports children's attention and learning readiness. This study enriches the literature review by integrating postural control maturity, attention, and learning readiness in young children, which are still rarely studied together Keywords: Postural Control, Attention, Children's Academics, early childhood